Between the Devil and the Deep Blue Sea: Enhancing Flexibility in International Climate Change Law. (17th June 2015) - Asselt, Harro van
Abstract: The evolving nature of the climate change problem makes it challenging to govern it through a single set of rules fixed in time. Scientific insights into the causes and impacts of climate change are subject to constant changes. Further, the socio-economic and political conditions prevailing in different countries continue to alter over time. This chapter first assesses how the primary international legal response, the regime established by the United Nations Framework Convention on Climate Change, has sought to cope with these temporal challenges, and suggests that while various flexibility mechanisms are in place, the climate regime often finds it hard to adapt to changing conditions. In a second step, the chapter examines an alternative in the form of proposals that aim to make international climate change law more adaptive through a pluralist approach. The chapter critically reviews these proposals, and suggests that while the rigidities of the existing climate regime certainly need to be addressed, considerations of predictability and stability should not be sacrificed at the altar of flexibility. To conclude, therefore, the chapter explores the options for enhancing flexibility within the current architecture for international climate change law.